MASALAH PENGENAAN PAJAK DAN UPAYA MENGHINDARI DITINJAU DARI TEORI EKONOMI MIKRO - Sardjono, Sigit (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2009)
The tax constitutes the important fund source for the development cost, thus it needs the efforts to do for intensification of fund taking. The success of these efforts will be determined by two related things, namely the society’s awareness to pay the tax  and the attitude and the ability of the tax authority in doing its duty in the field. The most fundamental problem in the tax aspect is actually located in the efforts for finding the answer, who receives the last tax load in the next turn. Is the last tax load taken by every person paying amount of money to the state’s revenue? Not certainly. Because it is still potential to shift the tax load, partly or overall, to other people. In public economy, the concept of tax load shift and the last tax load (tax incidence) is an important concept to be understood. The company revenue’s last tax load or incidence is a controversial case, from both the theoretical study and the empirical study. The resolution toward this case becomes interesting and important to be learned, so the related practitioners can determine and implement the tax policy more carefully. The critical point in this problem is located in “how to determine the last load receiver, that will carry implication toward the society’s income distribution.Key word : Shifting Tax; Tax Incidence; Theory MicroThe tax constitutes the important fund source for the development cost, thus it needs the efforts to do for intensification of fund taking. The success of these efforts will be determined by two related things, namely the society’s awareness to pay the tax  and the attitude and the ability of the tax authority in doing its duty in the field. The most fundamental problem in the tax aspect is actually located in the efforts for finding the answer, who receives the last tax load in the next turn. Is the last tax load taken by every person paying amount of money to the state’s revenue? Not certainly. Because it is still potential to shift the tax load, partly or overall, to other people. In public economy, the concept of tax load shift and the last tax load (tax incidence) is an important concept to be understood. The company revenue’s last tax load or incidence is a controversial case, from both the theoretical study and the empirical study. The resolution toward this case becomes interesting and important to be learned, so the related practitioners can determine and implement the tax policy more carefully. The critical point in this problem is located in “how to determine the last load receiver, that will carry implication toward the society’s income distribution.Key word : Shifting Tax; Tax Incidence; Theory MicroThe tax constitutes the important fund source for the development cost, thus it needs the efforts to do for intensification of fund taking. The success of these efforts will be determined by two related things, namely the society’s awareness to pay the tax  and the attitude and the ability of the tax authority in doing its duty in the field. The most fundamental problem in the tax aspect is actually located in the efforts for finding the answer, who receives the last tax load in the next turn. Is the last tax load taken by every person paying amount of money to the state’s revenue? Not certainly. Because it is still potential to shift the tax load, partly or overall, to other people. In public economy, the concept of tax load shift and the last tax load (tax incidence) is an important concept to be understood. The company revenue’s last tax load or incidence is a controversial case, from both the theoretical study and the empirical study. The resolution toward this case becomes interesting and important to be learned, so the related practitioners can determine and implement the tax policy more carefully. The critical point in this problem is located in “how to determine the last load receiver, that will carry implication toward the society’s income distribution.Key word : Shifting Tax; Tax Incidence; Theory Micro